Market performance and supply chain selection dynamics for vegetables grown through sustainable practices in the Northwest Himalayan region - Ajay Kumar; Divyanshu; Raghubir Singh Prashar; Rajeshwar Singh Chandel; Inder Dev; Subhash Sharma; Piyush Mehta; Rohit Kumar Vashishat (Frontiers in Sustainable Food Systems)
The production of marketable vegetable crops in the Northwest Himalayan region is crucial for bolstering the economy and sustaining the livelihoods of farming communities in the area. The factors influencing vegetable crop production, marketing, and farmer livelihoods include the selection of output market supply chains. Recognizing the importance of these aspects, this study examines the key determinants influencing farmers’ decisions regarding marketing supply chain selection. The study has highlighted the socio-economic dimensions of the area and its dwellers, further attempted to understand the cost of natural farming cultivation, followed by understanding the resource utilization in the natural farming practices, analytical representation of marketing components associated with the natural farming cultivation, and also attempted to analyze the key production and marketing problems associated with the natural farming. The concerned study has presented the analytical aspects of marketing supply chains comprehensively. The findings revealed that three primary marketing supply chains were prevalent in the study area. Among these, SC - C (Producer-Local Trader-Wholesaler-Retailer-Consumer) was the most commonly used, with 63% of the produce marketed through this supply chain, reflecting a preference for intermediary-based systems due to limited direct market access. The study reported facing significant marketing challenges, including a lack of access to specialized markets, an absence of fair pricing, and inadequate government support. Moreover, issues such as wholesalers not consulting farmers while selling their produce, lack of training and extension services, and poor market infrastructure were highlighted as key constraints. These marketing problems hinder farmers from obtaining fair value for their natural farming produce. The study emphasizes the need for improved market access, enhanced training facilities, and policy interventions to address these challenges and improve the overall marketing efficiency of natural farming systems in the region.